PENGGUNAAN PENDEKATAN KETERAMPILAN PROSES DALAM MENINGKATKANPRESTASI BELAJAR MATA PELAJARAN IPA - Aswida, Lili (WAHANA PEDAGOGIKA, 2016)
This study aimed to Improve the learning achievement of Science to the sixth graders in the even semester at the second state Elementary School Sidomulyo, Deket - Lamongan. The study used a design that consists of several cycles. One cycle consisted of four activities, namely: (1) Pre - reflection, (2) Planning, (3) The implementation and monitoring, (4) Reflection. The test results were shaped board has demonstrated optimal results. Results of the final test which included items A, namely the activities of children in the group with an average of 4. Item B: the ability to conclude with an average of 4.5. Item C was the ability of learners in completing or answering the test with an average of 8.05. And the overall average result of 8.35. Based on the discussion briefly be summarized as follows: The use of Skills Process could improve the learning achievement of Science to the sixth graders in the even semester at the second state Elementary School Sidomulyo, Deket â Lamongan.